2021
DOI: 10.1111/1477-9552.12459
|View full text |Cite
|
Sign up to set email alerts
|

Returns on investment to the British bovine tuberculosis control programme

Abstract: In the animal health arena, government-mandated testing, herd movement restrictions, and culling of reactor (infected) animals are common practices in the midst of an infectious disease outbreak. These policies create a significant economic trade-off-on one hand, such control efforts represent a public good by reducing the negative externality of private actions associated with the transmission of infectious disease; on the other hand, they impose substantial economic costs on the affected farms. This paper em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Maintaining good animal health is important for farm businesses; and livestock disease outbreaks can have considerable economic consequences affecting trade, food prices, and public health ( Hennessy and Wolf, 2018 ). Government control efforts, such as government-mandated testing, herd movement restrictions, and culling of reactor animals to eliminate diseases, are often a last resort, which is cost-effective ( Schaefer et al, 2021 ). Specifically, Schaefer et al (2021) showed that government control efforts on bovine tuberculosis (BTB) generated a positive external value for the British beef sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintaining good animal health is important for farm businesses; and livestock disease outbreaks can have considerable economic consequences affecting trade, food prices, and public health ( Hennessy and Wolf, 2018 ). Government control efforts, such as government-mandated testing, herd movement restrictions, and culling of reactor animals to eliminate diseases, are often a last resort, which is cost-effective ( Schaefer et al, 2021 ). Specifically, Schaefer et al (2021) showed that government control efforts on bovine tuberculosis (BTB) generated a positive external value for the British beef sector.…”
Section: Introductionmentioning
confidence: 99%
“…Government control efforts, such as government-mandated testing, herd movement restrictions, and culling of reactor animals to eliminate diseases, are often a last resort, which is cost-effective ( Schaefer et al, 2021 ). Specifically, Schaefer et al (2021) showed that government control efforts on bovine tuberculosis (BTB) generated a positive external value for the British beef sector. Thus, implementing farm-specific biosecurity plans can help to mitigate disease spread in the first place, and as such avoid ‘last resort’ measures.…”
Section: Introductionmentioning
confidence: 99%